2012
DOI: 10.1016/j.ssresearch.2012.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Family structure and the reproduction of inequality: Parents’ contribution to children’s college costs

Abstract: This article examines the role of family structure in the financial support parents provide for their children’s college education. Data are from the Health and Retirement Study. We focus on aspects of family structure that affect parental support and estimate shared family variance in investments as well as within-family variation using a multilevel model. Family membership accounts for about 60% of the variance in payment of college costs. Small family size, living with both biological parents (compared to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 33 publications
3
28
0
1
Order By: Relevance
“…Resource depletion theory suggests children who grow up in larger families receive fewer parental resources because of competing demands from other children in the family (Strohschein, Gauthier, Campbell, & Kleparchuk, 2008). Likewise, in adulthood grown children in larger families receive less parental support and less funding for college than the average child in smaller families (Fingerman et al, 2009; Henretta et al, 2012). …”
Section: Family Context Of Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Resource depletion theory suggests children who grow up in larger families receive fewer parental resources because of competing demands from other children in the family (Strohschein, Gauthier, Campbell, & Kleparchuk, 2008). Likewise, in adulthood grown children in larger families receive less parental support and less funding for college than the average child in smaller families (Fingerman et al, 2009; Henretta et al, 2012). …”
Section: Family Context Of Supportmentioning
confidence: 99%
“…For example, student status is associated with parental support. Upper SES parents offer financial resources to pay for their children’s higher education (Henretta et al, 2012) and other types of support during college (Attias-Donfut & Wolff, 2000; Fingerman et al, 2009; Fingerman, Cheng, Wesselmann, et al, 2012). …”
Section: Offspring Factors That Elicit Supportmentioning
confidence: 99%
“…A preliminary study conducted 30 years ago indicated that among White, middle class stepfamilies, stepfathers contributed approximately 50 % of the financial support for their stepchildren (Giles-Sims and Crosbie-Burnett 1989): clearly more recent and comprehensive information would be valuable. There is some evidence that remarried couples are more likely to keep finances separate than in first marriages, particularly when both adults have biological children (Burgoyne 1997;Coleman and Ganong 1989), and that college-aged stepchildren receive less financial support than children whose parents are married to each other J Fam Econ Iss (2016) 37:285-296 293 (Henretta et al 2012;Turley and Desmond 2010;Zvoch 1999). Understanding the actual levels of support provided to stepchildren (including children and adolescents), and the factors related to levels of support would assist in ensuring policies do not excessively disadvantage stepchildren.…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…There is also a clear need for more research with stepfamily members regarding their attitudes to supporting stepchildren, as well as how much support is actually provided and in what circumstances. Research for instance is needed regarding whether the lower support for university-aged stepchildren observed in the US (Henretta et al 2012;Turley and Desmond 2010;Zvoch 1999) occurs in Australia and whether this impedes access to education. Investigation of whether similar reductions in support also apply to school-aged children should also be investigated.…”
Section: Conclusion and Research Implicationsmentioning
confidence: 99%
“…Writing before the recession was fully upon us Settersten (2007c) noted the mounting significance of social class, the focus of the Occupy movement, in shaping life chances as individuals rely more heavily on personal social networks for support. In keeping with cumulative disadvantage and the significance of family lineage to inequality (Ferraro & Shippee, 2009), young adults from better-off families receive more financial help from their parents, and adult children experience long-term benefits in socioeconomic status from such help (Fingerman, Cheng, Tighe, Birditt, & Zarit, 2012;Henretta, Wolf, Van Voorhis, & Soldo, 2012;Swartz, 2008;see also McDaniel et al, 2013). Thus, having to rely on support within families magnifies inequality outside them.…”
Section: Intergenerational Ties: Inside Familiesmentioning
confidence: 99%